Wonder horse - McCully, Emily Arnold (Henry Holt, 2010)
A fictionalized account of Bill "Doc" Key, a former slave who became a veterinarian, trained his horse, Jim Key, to recognize letters and numbers and to perform in skits around the country, and moved the nation toward a belief in treating animals humanely. Includes an author's note.